Neurogenic Bladder and Acute Kidney Injury in Leukodystrophy - Kemec, Zeki; Tuzun, Cevat; Gurel, Ali (Springernature, 2020)
Leukodystrophies are genetic white matter disorders. In the young, they represent an important cause of progressive neurological disability. Impairment of the bladder function may be part of the clinical picture of leukodystrophies. A neurogenic bladder is a dysfunctional urinary bladder caused by a disease of the central or peripheral nervous system involved in the control of micturition. In our patient, leukodystrophy-induced neurogenic bladder and acute kidney injury were revealed. If untreated, a neurogenic bladder can cause renal failure and urinary incontinence. Patients with a neurogenic bladder should be monitored, and management should aim to preserve renal function and achieve social continence.
Keywords: leukodystrophy; neurogenic bladder; acute kidney injury